Estradiol up-regulates c-FLIPlong expression in anterior pituitary cells - Jaita, Gabriela Alejandra (2016)
Anterior pituitary cell turnover depends on a tight balance between proliferation and apoptosis. We have previously shown that estrogens sensitize anterior pituitary cells to pro-apoptotic stimuli. c-FLIP (cellular-FLICE-inhibitory-protein) isoforms are regulatory proteins of apoptosis triggered by death receptors. c-FLIPshort isoform competes with procaspase-8 inhibiting its activation. However, c-FLIPlong isoform may have a pro- or anti-apoptotic function depending on its expression level. In the present study, we explored whether estrogens modulate c-FLIP expression in anterior pituitary cells from ovariectomized (OVX) rats and in GH3 cells, a somatolactotrope cell line. Acute administration of 17β-estradiol to OVX rats increased c-FLIPlong expression in the anterior pituitary gland without changing c-FLIPshort expression as assessed by Western blot. Estradiol in vitro also increased c-FLIPlong expression in anterior pituitary cells but not in GH3 cells. As determined by flow cytometry, the percentage of anterior pituitary cells expressing c-FLIP was higher than in GH3 cells. However, c-FLIP fluorescence intensity in GH3 cells was higher than in anterior pituitary cells. FasL increased the percentage of TUNEL-positive GH3 cells incubated either with or without estradiol suggesting that the pro-apoptotic action of Fas activation is estrogen-independent. Our results show that unlike what happens in nontumoral pituitary cells, estrogens do not modulate either c-FLIPlong expression or FasL-induced apoptosis in GH3 cells. The stimulatory effect of estradiol on c-FLIPlong expression could be involved in the sensitizing effect of this steroid to apoptosis in anterior pituitary cells. The absence of this estrogenic action in tumor pituitary cells could be involved in their tumor-like behavior.